UMPAK-UMPAK DI SITUS CANDI SANGGAR - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2009)
Artifacts, such as ceramics, potteries, and 18 propstones are found in the vicinity of Chandi Sanggar. By analyzing the propstones, it turned out that they have many varieties on the size, and the technology. It is remarkable to observe that the surface of the propstones showed variants: smooth, rough, and the combination of it, whereas their size are also different: big, medium, and small. The differences are related to the structure of Chandi Sanggar, since the propstones were found in context with it. Therefore it can be concluded that Chandi Sanggar was a compound, consisted of the main chandi and several supporting buildings.